THE APPLICATION OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SQUARE SHARE (TPSS) ON SPLTV MATERIAL IN CLASS X BAITUSSALAM SENIOR HIGH SCHOOL - Rahmat Fitra; Rauzatul Jannah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
One of the problems encountered in learning mathematics is that students still have difficulty when solving problems that require reasoning and accuracy. This condition is caused by various factors, one of which is the learning model used by the teacher. This study aims to determine the learning success of students taught with the TPSS type cooperative learning model on SPLTV material and to describe student activities during the learning process. This research used quantitative approach with pretest posttest group design. The research population was 160 students of class X, while the research sample was X-IPA 1 class with 27 students. Data collection was done through tests and observations, the collected data were analysed using statistical tests (t-test). The results showed that: (1) there is an increase in student learning outcomes taught using the TPSS model as seen through the difference in the mean scores of the pretest and posttest which increased from 44.83 to 75.76 with a difference of 30.93. The hypothesis test results show the value of tcount> ttable (4.46 > 1.71) so it is concluded that students taught with the TPSS type cooperative learning model on SPLTV material can achieve learning success. (2) Student activity in learning using the TPSS model on SPLTV material is included in the good category with a percentage of 80%.